Left atrial myxoma development after radiofrequency ablation of an atrial flutter substrate. Issue 4 (April 2015) - Santillo, Elpidio; Migale, Monica; Marini, Luciano; Fallavollita, Luca; Massini, Carlo; Balestrini, Fabrizio
Abstract: A 51-year-old man developed symptoms (palpitations) related to a large left atrial mass attached to interatrial septum discovered by trans-thoracic heart ultrasonography. Six months earlier this patient had undergone radiofrequency ablation (RFA) of an atrial flutter substrate. The left atrial mass was removed surgically using cardiopulmonary bypass with disappearance of symptoms. A post-operative diagnosis of atrial myxoma was made. The present case shows that a big left-atrial tumor could manifest with only mild unspecific symptoms such as palpitations. It is not clear whether the development of myxomas could be related to RFA or occurrence of heart tumors after RFA (already reported in medical literature) or whether it could be just chance without a causal link with ablation procedures. <Learning objective: It is essential to consider myxoma in the differential diagnosis of cardiac masses identified in patients after radiofrequency ablation since some cases of myxoma development after radiofrequency ablation have recently been described in the literature. Transthoracic echocardiography is a precise technique in the evaluation of cardiac masses, but a high index of clinical suspicion is necessary in order to define intracardiac pathologies that could be missed for unspecific symptoms of presentation.>